2021
DOI: 10.1186/s13287-021-02187-y
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA TTC3 regulates cerebral ischemia-reperfusion injury and neural stem cells by miR-372-3p/TLR4 axis in cerebral infarction

Abstract: Background Stroke serves as a prevalent cerebrovascular disorder with severe cerebral ischemia/reperfusion (CIR) injury, in which neural stem cells (NSCs) play critical roles in the recovery of cerebral function. Circular RNAs (circRNAs) have been widely found to participate in stroke and NSC modulation. However, the role of circRNA TTC3 (circTTC3) in the regulation of CIR injury and NSCs remains elusive. Here, we aimed to explore the impact of circTTC3 on CIR injury and NSCs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…In this review, the lncRNA/circRNA-miRNA-mRNA regulatory network also exists in microglia and astrocyte mediated neurological diseases, including SCI (Figure 1; Shao et al, 2020; FIGURE 1 | The lncRNA/circRNA-miRNA-mRNA regulatory network in microglia and astrocyte regulated neurological diseases. Xu S. et al, 2020;Zhao Q. et al, 2020;Cui et al, 2021;Xiang et al, 2021;Chen et al, 2022), TBI (He et al, 2021;Liu N. et al, 2021;Meng et al, 2021), cerebral IRI (Figure 1; Wang et al, 2020c;Yang et al, 2021), stroke (Figure 1; Qi et al, 2017;Han B. et al, 2018;Tian et al, 2021;Zhang M. et al, 2021), epilepsy (Figure 1; Feng et al, 2020;Han C. L. et al, 2020;Wan and Yang, 2020;Xiaoying et al, 2020), neuropathic pain (Figure 1; Chen M. et al, 2020), PD (Figure 1; Cao et al, 2018Cao et al, , 2021, and depression (Figure 1; . We also found that some therapies can impair the ncRNA-glial cell axis and thus inhibit disease development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, the lncRNA/circRNA-miRNA-mRNA regulatory network also exists in microglia and astrocyte mediated neurological diseases, including SCI (Figure 1; Shao et al, 2020; FIGURE 1 | The lncRNA/circRNA-miRNA-mRNA regulatory network in microglia and astrocyte regulated neurological diseases. Xu S. et al, 2020;Zhao Q. et al, 2020;Cui et al, 2021;Xiang et al, 2021;Chen et al, 2022), TBI (He et al, 2021;Liu N. et al, 2021;Meng et al, 2021), cerebral IRI (Figure 1; Wang et al, 2020c;Yang et al, 2021), stroke (Figure 1; Qi et al, 2017;Han B. et al, 2018;Tian et al, 2021;Zhang M. et al, 2021), epilepsy (Figure 1; Feng et al, 2020;Han C. L. et al, 2020;Wan and Yang, 2020;Xiaoying et al, 2020), neuropathic pain (Figure 1; Chen M. et al, 2020), PD (Figure 1; Cao et al, 2018Cao et al, , 2021, and depression (Figure 1; . We also found that some therapies can impair the ncRNA-glial cell axis and thus inhibit disease development.…”
Section: Discussionmentioning
confidence: 99%
“…Depleting circTTC3 suppresses OGD-induced astrocyte injury and promotes NSC proliferation and differentiation via the miR-372-3p-TLR4 axis. The circTTC3 knockdown in MCAO/R mice can alleviate cerebral IRI (Yang et al, 2021).…”
Section: Ischemia-reperfusion Injurymentioning
confidence: 97%
“…For instance, circRNA_2837 targets miR-34 family members to regulate LC3-II/p62 and protect neurons by autophagy in the sciatic nerve injury model (Zhou et al, 2018). In neural stem cells, circRNA TTC3 sponges miR-372-3p to regulate TLR4 expression and prevent cerebral ischemia reperfusion injury (Yang et al, 2021). With a new understanding of the ceRNA networks in different diseases, therapies targeting ceRNAs rather than miRNAs alone may become more significant and valuable (Bak and Mikkelsen, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These then participate in the process of brain repair and play an essential role in IS ( 84 ). Yang et al explored the effects of circRNA-TTC3 on ischemia-reperfusion injury and NSCs ( 85 ). TTC3 expression was significantly increased in hypoxic astrocytes, and its target was miR-372-3p.…”
Section: Ncrna Regulatory Network In Ischemic Strokementioning
confidence: 99%